Diabetes Distal Peripheral Neuropathy: Subtypes and Diagnostic and Screening Technologies. (March 2022) - Newlin Lew, Kelley; Arnold, Tracey; Cantelmo, Catherine; Jacque, Francky; Posada-Quintero, Hugo; Luthra, Pooja; Chon, Ki H.
Diabetes distal symmetrical peripheral neuropathy (DSPN) is the most prevalent form of neuropathy in industrialized countries, substantially increasing risk for morbidity and pre-mature mortality. DSPN may manifest with small-fiber disease, large-fiber disease, or a combination of both. This review summarizes: (1) DSPN subtypes (small- and large-fiber disease) with attention to clinical signs and patient symptoms; and (2) technological diagnosis and screening for large- and small-fiber disease with inclusion of a comprehensive literature review of published studies from 2015-present ( N = 66). Review findings, informed by the most up-to-date research, advance critical understanding of DSPN large- and small-fiber screening technologies, including those designed for point-of-care use in primary care and endocrinology practices.